KETIDAKNYAMANAN PASCA PERSALINAN: ANALISIS KONSEPTUAL DAMPAK DIASTASIS RECTUS ABDOMINIS (DRA) TERHADAP IBU POSTPARTUM - Hemi Fitriani; Setyowati Setyowati; Yati Afiyanti; Yeni Rustina (Poltekkes Kemenkes Bandung, 2025)
Diastasis rectus abdominis (DRA) in postpartum mothers has a high prevalence, with 85% experiencing this condition, leading to various complaints. However, clinical management remains limited due to the lack of consensus on symptom boundaries and clinical impacts. This study aims to analyze the concept of discomfort due to DRA in postpartum mothers using Walker and Avant’s approach. A descriptive method with concept analysis was applied. Literature search using international electronic databases with a global scope including Scopus, ScienceDirect, MEDLINE, EBSCO, ProQuest, and SAGE, using keywords such as